Research and evaluation calculate passenger car ranges County HMK29SL in the company of assembly Tracomeco - Lâm Mai Long; Lâm Văn Quốc (Journal of Technical Education Science, 2013)
Today, the automobile industry, many units, the group have focused on the study of oscillations in order to create kind of car are smooth response, safety in motion with conditions different infrastructure in each country. This paper presents building research programs to solve calculation ranged automobile by creating interface toolkit calculated using the Matlab Graphics User Interface to facilitate the use of design parameters new design or renovation design, conversion design and suspension changes on the optimal range. In order to test and evaluate the comparative smooth movement of cars in general and County HMK29SL particular bus.